Study on the reference of Russian ice-snow sports resources for the cultivation of ice-snow sports talents of colleges and universities - Li, C. (Advances in Social Science, Education and Humanities Research, 2018)
This article is the key project of the "Thirteenth Five-Year Plan" of Heilongjiang Province: innovative research on Sino-Russian joint cultivation of ice-snow sports talents in colleges and universities under the perspective of "supply-side reform". In summary, as far as the current situation of ice-snow sports talents training in colleges and universities is concerned, there are still many problems in carrying out icesnow sports teaching and talent training such as limited funds, difficulty in paying high venue funding, transportation funds and academic aid funds, lack of teaching innovation consciousness, monotonous content of ice-snow sports teaching, difficulty in forming characteristic ice-snow physical education curriculum; single curriculum model; incomplete professional faculty and team. In order to highlight the development of ice-snow sports education and strengthen the training of China's ice-snow sports reserve talents, it still needs school and enterprise to carry out multiparty cooperation, jointly advocate and active use superior resources to promote the development of China's ice-snow sports talents to a higher level and specialized direction together.